PENGARUH PRODUCT PLACEMENT, CELEBRITY ENDORSER, BRAND AWARENESS TERHADAP PURCHASE INTENTION KOPIKO PADA DRAMA KOREA VINCENZO - Novianti, (2022)
This study was conducted to find out the influence of product placement, supporting celebrities and brand awareness on consumer's purchase intentions of Kopiko coffee candy products in a Korean drama called "Vincenzo". This research is quantitative research by using primary data sources. The research object will be using 100 respondents selected with purposive sampling techniques. The research data will be analyze using descriptive and inferential analysis techniques. Data were collected through questionnaires and tested using the PLS statistical testing tool (Partial Least Square). Data processed with Smart PLS shows: (1) Product Placement have significant influence on purchase intention, (2) Celebrity Endorser have significant influence on purchase intention, (3) Brand Awareness have significant influence on purchase purchase intention.